Influence Skills and Intelligence Emotional to Commitment Organization With Motivation Work As Intervening Variables in BPJS North Sumatra Region - Netty Helena Br Sigalingging; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
In this study, researchers wanted to see the direct and indirect effects between the variables of skills and emotional intelligence as independent variables and work motivation as a moderating variable and Organizational Commitment as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS Ketenagakerjaan North Sumatra Region. The population of this study were 60 employees and the sample used was the entire population using the saturated sample technique. The data source used is primary data source and data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows work skills have a positive and insignificant effect on work motivation with an original sample value of 0.275 and p values of 0.381. Job skills have a positive and significant effect on organizational commitment with an original sample value of 0.580 and p values of 0.000. Emotional intelligence has a positive and significant effect on work motivation with an original sample value of 0.570 and p values of 0.001. Emotional intelligence has a positive and insignificant effect on organizational commitment with an original sample value of 0.117 and p values of 0.612. Emotional intelligence has a positive and significant effect on organizational commitment through work motivation directly with original sample results of 0.179 and p values of 0.001. Job skills have a positive and insignificant effect on organizational commitment through work motivation with an original sample value of 0.181 and p values of 0.388.